2020
DOI: 10.3892/ijo.2020.5039
|View full text |Cite
|
Sign up to set email alerts
|

CDH1 and SNAI1 are regulated by E7 from human papillomavirus types 16 and 18

Abstract: A common characteristic of cancer types associated with viruses is the dysregulated expression of the CDH1 gene, which encodes E-cadherin, in general by activation of DNA methyltransferases (Dnmts). In cervical cancer, E7 protein from high risk human papillomaviruses (HPVs) has been demonstrated to interact with Dnmt1 and histone deacetylase type 1 (HDAC1). The present study proposed that E7 may regulate the expression of CDH1 through two pathways: i) Epigenetic, including DNA methylation; and ii) Epigenetic-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 70 publications
(96 reference statements)
0
10
0
Order By: Relevance
“…According to recent study of Rosendo-Chalma and collaborators, different from SiHa and Hela cell lines that showed mesenchymal-like phenotype, the Caski cells exhibit an epithelial phenotype which seems to reflect the impact of their distinct microenvironment. 33 The datasets using CSC-like derived from pharyngeal (GSE97510) and pancreatic (GSE36563) tumour cells did not present statistical differences when compared to adherent/monolayer cells.…”
Section: Discussionmentioning
confidence: 89%
“…According to recent study of Rosendo-Chalma and collaborators, different from SiHa and Hela cell lines that showed mesenchymal-like phenotype, the Caski cells exhibit an epithelial phenotype which seems to reflect the impact of their distinct microenvironment. 33 The datasets using CSC-like derived from pharyngeal (GSE97510) and pancreatic (GSE36563) tumour cells did not present statistical differences when compared to adherent/monolayer cells.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, we have observed that independent of the HPV genotype, cell lines derived from CC tumors can exhibit different CD73 expression levels and Ado generation capabilities 27 . Additionally, differences in cellular phenotypes have been reported, probably due to the microenvironment of origin; for instance, SiHa and HeLa cell lines show a mesenchymal‐like phenotype, while CaSki cells, which were obtained from omentum metastases, exhibit an epithelial phenotype 52 . In addition, CD73 function can differ in the same cell type from different tissues and within tumors, and the tumor cells themselves can differ in relation to CD73 expression compared to adjacent stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Additionally, differences in cellular phenotypes have been reported, probably due to the microenvironment of origin; for instance, SiHa and HeLa cell lines show a mesenchymal‐like phenotype, while CaSki cells, which were obtained from omentum metastases, exhibit an epithelial phenotype. 52 In addition, CD73 function can differ in the same cell type from different tissues and within tumors, and the tumor cells themselves can differ in relation to CD73 expression compared to adjacent stromal cells. The expression and activity of CD73 may also diverge depending on the stage of tumor development and different factors in the microenvironment leading to tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…In HPV‐induced cervical cancer, E‐cadherin expression is downregulated, while Snail and ZEB1 are markedly upregulated 183 . HR‐HPV E5/E7 is also implicated in this regulation 184,185 . Furthermore, HPV16/18 E7 curtails CDH1 and SNAI1 via DNA methylation 185 .…”
Section: Hpv and Its Pathogenesismentioning
confidence: 99%